PEMANFAATAN BONGGOL PISANG (Musa paradisiaca L.) DALAM RANSUM TERHADAP PERFORMA AYAM BROILER - Kupai, Kidejus; Mandey, J S; Kowel, Y H.S; Regar, M N (ZOOTEC, 2020)
UTILIZATION Â OF BANANA CORM (Musa paradisiaca L.) IN DIET ON BROILER CHICKENS PERFORMANCE. The research on the utilization of banana (Musa paradisiacaL.) corm in broiler diet aimed to determine its effect on the performance of broilers, namely the feed intake, weight gain, and feed conversion ratio. The birds used were 100 unsexed days old chicks. This study used a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. The composition of the treatment as follows: R0 = 55% corn + 0% banana corm meal (BCM), R1 = 50% corn + 5% BCM, R2 = 45% corn + 10% BCM, R3 = 40% corn + 15% BCM. The result showed that the treatment had a significantly different effect on feedintake, body weight, and feed conversion ratio. Based on the results of the study, it was concluded that banana corm can be used up to 10% in broiler chicken diet.